Exploring the Confluence of Financial Innovation, Human Resource Strategies, and Marketing Management: A Systematic Literature Review on Profit Maximization and Business Attraction - Djaharuddin, Dharmawaty; Hasbiyadi, Hasbiyadi; Syamsu, Nur; Themba, Orfyani S; Mochtar, Susianah; Tafsir, Muh. (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aims to explore the intricate relationships between financial innovation, human resource (HR) strategies, and marketing management, and how their integration drives organizational success, particularly in terms of profitability and business attraction. Utilizing a systematic literature review, the research synthesizes findings from various academic sources to provide a balanced and comprehensive understanding of these interdependencies. The methodology focuses on analyzing the existing literature to identify the conditions under which financial innovation, HR strategies, and marketing management can be most effectively integrated. The results indicate that financial innovations such as fintech and blockchain significantly enhance organizational profitability when aligned with strategic HR practices and customer-centric marketing approaches. The study further reveals that the successful implementation of these innovations requires substantial investments in employee training and adaptive marketing strategies that resonate with consumer needs. The findings underscore the importance of adopting a holistic approach, where financial innovation, HR, and marketing are treated as interconnected components of a unified business strategy. This integration not only enhances competitiveness but also positions organizations to navigate the challenges of a rapidly evolving business environment. The study offers valuable theoretical and managerial implications, providing a framework for future research and practical guidance for business leaders and policymakers on leveraging these domains for sustainable growth.